ANALISIS SYISTEM METODOLOGI DAN FILSAFAT HUKUM ISLAM (Analisis Terhadap Pemikiran Jasser Auda) - Muhammad Kholil (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2018)
The development and changes of social society is increasingly complex, ranging from social problems, humanities and even legal issues often appear and sometimes make it difficult for the community in determining its status. Therefore, the issue needs intelligence and sharpness of sensitivity or high and sensitive to the situationand conditions, then it be able to reduce the problem of conflict. It takesthinkers and scholars contemporary who are able to provide insight to solve a problem. The maqasid al-syari'ah described abstract although there are already Islamic thinkers who try to explain maqasud al-syari'ah in terms of theory and methodology, but still "grope". This is natural,maqasid al-syariah seeks to change the way of thinking of the classical scholars and still includedthe norms of the basic philosophical values. it is need for further Muslim thinkers to contribute their thoughts of a more systematic maqasid al-syri'ah creation, is a shift paradigm from the old maqasid to the new maqasid. The old maqasid emphasizes on protection (protection) more and perservation.New maqasid emphasizes more on devolopment (development) and righ (right). Welfareof the child's soul protection (hifdzu al-nafs).